Synthesis and Characterization of Nanocrystalline M-Mg-O and Carbon-Coated MgO Systems; Materials Science Forum; Vol. 917 - Karnaukhov T. M. Timofey Mikhaylovich; Vedyagin A. A. Aleksey Anatolievich; Mishakov I. V. Iljya Vladimirovich; Bedilo A. F. Aleksandr; Volodin A. M. Aleksandr (2018, 2018)
Title screen